Digital Collaboration Tools and Operations Management - Prokop, Jan (2020)
This thesis describes the main benefits of Ecommerce. Due to the fact that Ecommerce company can be operated from anywhere in the world, a set of smart performance management tools is beneficial. In order for the tools to be managed properly, the methods of Operations management are essential. For practical part, an examination of the processes of a product management in a small Czech Ecommerce store is provided. This process is digitalized with collaboration tools such as Trello or Slack. The whole procedure is thoroughly analysed both with SIPOC analysis and Flowcharts. The changes are monitored based on principles from Operations management, more specifically with Five Performance Objectives framework. As a result, a list of recommendations is provided as a handful tool for managers and company owners who consider upgrading their processes to the digitalized form. From a management perspective, the digitalization improves overall efficiency of the process of product management.